Going Beyond Institutional Pressures: Reviewing Adoption of ISO 14001 at the Gorman-Rupp Company. - Bores, Jessica (2011)
Having reviewed the research on ISO 14001 adoption, it was found there was a “gap” in the research overall related to the size of organizations reviewed and level of analysis. Therefore this dissertation looked to fill this gap by conducting a case-study at the Gorman-Rupp Company with a focus on the organization’s top-management. The aim of this research was to understand how individuals viewed institutional pressures and to explore how that impacted adoption of ISO 14001. What has been found is that it is not as much about the institutional pressure, but rather the level of understanding of those involved. This research thus suggests the need to develop understanding of ISO 14001 within an organization, specifically individual understanding, if the ISO 14001 EMS is to go beyond just complying with the institutional pressures related to adoption.